ASSESSING COFFEE ECOTOURISM STRENGTHS AND CHALLENGES IN CIBULAO VILLAGE THROUGH STORY MAPS - Surya Hafizh; Dipo Caesario; Anisha Syafitri Tanjung; Rizki Zakiah; Silvia Novita; Dhea Sonya; Yunaldo Dwi Cahyadi; Rivantia Azzahra (Jurnal Belantara, 2026)
Cibulao Village has significant potential for ecotourism development, particularly through coffee cultivation. However, this potential requires strategic planning and effective promotion. This study analyzes the strengths, weaknesses, opportunities, and challenges of coffee ecotourism in Cibulao Village and develops a promotional media that supported by geographic information system using the ArcGIS StoryMaps platform. The methods included interviews, observation, and documentation involving managers, tourists, and the local community. The research results show good potential in developing coffee ecotourism, such as a tourism concept that promotes education on conservation coffee cultivation area and sites but still faces challenges in infrastructure and limited development possibilities due to land ownership and area status. The development of ArcGIS StoryMaps can be an alternative interactive promotional media based on geographic information system technology that is more effective and efficient because it shows the potential strengths, weaknesses, opportunities, and challenges that are depicted in real time tracking map and storytelling.